Manajemen Perpustakaan Di Universitas Nahdlatul Ulama Al Ghazali - Albab, Ulil; Masfufah, Elok Zamzani (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2025)
This thesis research discusses the library management process at Nahdlatul Ulama Al GhazaliUniversity and what are the obstacles in implementing this management. The aim of this research is to find outhow library management is carried out by the Al Ghazali Library starting from the planning, organizing,implementing and monitoring stages as well as to find out the obstacles to the management process at the AlGhazali Library. In this research, the research subjects taken were the head of the library, the technicalservices sector, the reference services sector, and the library services sector. The data collection techniquesused by researchers used observation, interviews and documentation.The results of this research are library management which refers to national library standards whichinclude Library Collection Standards, Library Facilities and Infrastructure, Library Service Standards,Library Staff Standards, Library Administration, and Library Management Standards. Therefore, as a resultof this research, researchers found that every management process starting from planning, organizing,implementing and supervising was carried out by paying attention to the library's national standards.Keywords: Library Management, National Library Standards